The Potential of Acacia angustissima Leaf Meal as a Supplementary Feed Source in Broiler Finisher Diets - Ncube , S.; Hamudikuwanda, H.; Banda, P. (International Journal of Poultry Science, 2011)
This study evaluated, in a completely randomized design with five replicates, performance of Ross broiler chicks fed diets with 0 to 15% of Acacia angustissima leaf meal (leaf meal) from the fifth week to the end of the eight week of growth. Feed intake, weekly bodyweight, bodyweight gain, feed conversion ratio and carcass characteristics were determined. Feed intake, body weight gain and feed conversion ratio in birds on the 0% to 5% were not different (p